The effect of international trade on the economic progress of Kazakhstan: analysis and forecasts - Koptayeva, G.; Atenova, K.; Kosherbayeva, A.B.; Yessirkepova, А.; Saginova, S. (BUKETOV BUSINESS REVIEW, 2024)
Object: The investigation scrutinizes the impact of a country's involvement in global trade on its economic growth over the preceding decade. It encompasses an analysis of the quantity of exports and imports, the proportion of international trade in relation to GDP, alterations in trade composition, and various other pertinent factors. Methods: Compiling data on Kazakhstan's global trade dynamics spanning the last ten years, encompassing export and import volumes, trade structure, key partners, and other vital metrics. Investigating Kazakhstan's trade collaborators, discerning interaction patterns, and analyzing how changes in their economies affect Kazakhstan. The originality and significance of the research lie in its comprehensive exploration of how international trade influences Kazakhstan's development, considering aspects like economic growth, employment, and living standards. Delving deeply into the past decade facilitates the identification of enduring trends and factors influencing diverse facets of the country's progress. Findings: The investigation exposed the favorable influence of global trade on Kazakhstan's economic advancement in the preceding decades. The upsurge in both outbound and inbound trade was coupled with a sustained elevation in the nation's gross domestic product (GDP). Conclusions: They consist in a comprehensive analysis of the impact of international trade on the progress of Kazakhstan, combining aspects of economic growth, employment and living standards. Conducting in-depth research over the past decade allows us to identify stable trends and factors affecting various aspects of the country's development.